The effects of cycling cadence on the phases of joint power, crank power, force and force effectiveness - Ettema, G.; Lorås, H.; Leirdal, S. (Journal of Electromyography and Kinesiology, 2008)
We examined the influence of cadence in cycling technique by quantifying phase relationships for a number of important variables at the crank and lower extremity joints. Any difference in the effect of cadence on force, effectiveness, and power phases would indicate an essential change in coordination pattern. Cycle kinetics was recorded for 10 male competitive cyclists at five cadences (60-100 rpm) at submaximal load (260 W). Joint powers were calculated using inverse dynamics methods. All data were expressed as a function of crank position. The phase of the crank mechanical profiles (total force, crank and joint power, and effectiveness) was calculated using four methods: crank angle of maximum (MA) and minimum (MI), fitting a sine wave (SI) and by cross-correlation (XC). These methods, apart from the MA method, showed the same relative phase. The variables, however, showed different phases being expressed as time lag: force effectiveness: 0.131 (±0.034) s; total force: 0.149 (±0.021) s; power: 0.098 (±0.027) s. The phases in joint powers hip 0.071 (±0.008), knee 0.082 (±0.009), and hip 0.077 (±0.012) were only well described by XC, and were somewhat lower than the crank power phase. These differences indicate the potential effect of inertia of the lower limb in phase shifts from joints to crank. Furthermore, the differences between the various crank variables indicate a change of technique with cadence.